What should fiscal councils do? - Wren-Lewis, S; Calmfors, L (University of Oxford, 2011)
Fiscal councils now exist in a number of countries. This paper first considers the extent of deficit bias, potential explanations for it, and how independent institutions could help reduce it. Are fiscal councils complements to or substitutes for fiscal rules, and why do none at present have any formal control over fiscal decisions? The paper then outlines the specific tasks that a fiscal council might undertake, and examines how these are combined in eleven fiscal councils. A more detailed examination is undertaken of the fiscal councils in Sweden and the UK. The paper draws some conclusions on the role of fiscal forecasting, ensuring independence, and the provision of policy advice.